1994
DOI: 10.1002/mpo.2950220511
|View full text |Cite
|
Sign up to set email alerts
|

Predisposition to corynebacterium jeikeium infection in acute lymphoblastic leukemia: a report of two cases in trinidad

Abstract: Two hospitalized patients (a 4 and 6 year old male and female, respectively) with acute lymphoblastic leukaemia (ALL), had each at different periods sustained burns with necrosis from extravasation of chemotherapeutic products. Pure cultures from their wound exudates and blood repeatedly revealed Corynebacterium jeikeium, an organism recognized and identified in the last decade as an opportunistic cause of life-threatening nosocomial infections particularly in patients on long-term multiple antimicrobial thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…Both isolates were multiresistant with similar antibiogram and identified as Corynebacterium jeikeium. 9 The most frequently isolated pathogen was S. aureus (23.9%) and this is consistent with the general increase in Gram-positive infections worldwide. This high prevalence of infections due to S. aureus is similar to the 28% reported from Australia, 20 but higher than the 7-16% observed in India and Ethiopia.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Both isolates were multiresistant with similar antibiogram and identified as Corynebacterium jeikeium. 9 The most frequently isolated pathogen was S. aureus (23.9%) and this is consistent with the general increase in Gram-positive infections worldwide. This high prevalence of infections due to S. aureus is similar to the 28% reported from Australia, 20 but higher than the 7-16% observed in India and Ethiopia.…”
Section: Discussionsupporting
confidence: 77%
“…[1][2][3] Many studies on the incidence of blood stream infections have shown an increased occurrence over the past 15-20 years due to the increasingly vulnerable patient population being admitted to hospitals. 1,4 Patients at particular risk for bacteremia include those less than five years of age, 1,5 those with severe underlying disease, [6][7][8][9] the malnourished, 10 and those with severe burns and admission to an intensive care unit. [11][12][13] The majority of pediatric bacteremia cases are caused by a number of common pathogens that include Streptococcus pneumoniae, group B streptococci (GBS), Haemophilus influenzae, Escherichia coli, Pseudomonas aeruginosa, Klebsiella pneumoniae, Staphylococcus aureus, and Enterobacter spp, 1,4,7,14 and the predominant etiologic agent may vary from one geographical area to another, and even within a given area.…”
Section: Introductionmentioning
confidence: 99%
“…Corynebacterium jeikeium has been recognized as an important cause of infection, particularly among patients with underlying hematological malignancies or other conditions that cause immunosuppression 12–16. Risk factors that predispose individuals to infection include extended hospitalization, prolonged neutropenia, the presence of prosthetic devices (especially intravascular catheters), prior broad‐spectrum antibiotic therapy, and skin disruption 15, 16.…”
Section: Discussionmentioning
confidence: 99%
“…During the period in which she was found to be infected with C. jeikeium , she had several risk factors, including profound neutropenia, a CVC, and concurrent exposure to broad‐spectrum antibiotics. C. jeikeium can cause many types of infections, including bacteremia, neurosurgical shunt infections, endocarditis, epicardial and liver abscesses, and musculoskeletal infections 12–16. C. jeikeium strains are often resistant to various antibiotics 17.…”
Section: Discussionmentioning
confidence: 99%
“…Cutaneous manifestations of infection by C. jeikeium were described by Dan et al (100). More recently, AIDS with (413) and without (381) neutropenia, neutropenia (373), neoplasms (25,137), meningitis with transverse myelitis (217), cerebral ventriculitis (235), ventricular cerebrospinal fluid shunt infections (173), prosthetic and native heart valve endocarditis (432), osteomyelitis after total hip replacement (455), infectious arthritis after arthroplasty (465), and lymphadenopathy in a patient with Whipple's disease (339) have been reported as being associated with C. jeikeium infections. C. jeikeium was recently implicated as the cause of papular eruption with features histologically mimicking botryomycosis (220).…”
Section: Lipophilic Corynebacteriamentioning
confidence: 97%